2022
DOI: 10.1007/s40123-022-00496-w
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Location Between Tear Film Center and Corneal Vertex Following Small-Incision Lenticule Extraction

Abstract: Introduction We aimed to measure the relationship of location between the tear film center (TFC) and corneal vertex (CV) following small incision lenticule extraction (SMILE). Methods A total of 100 consecutive patients (100 eyes) who underwent the SMILE procedure were included. Screen captures of intraoperative videos and pupillary offset were analyzed. Location was compared using a vector plot for the two reference points. Results The arith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…Huang et al [26] even found that the decentration of EOZ centroid in both eyes was different (the right eye shifted superior while the left eye shifted to the nasal side), although both eyes were centered on the CV by the TFM method. The latest research showed that the TFM center can simulate the position of the CV accurately and indicated that the decentration of EOZ after the operation can be predicted in advance by observing the change of the TFM center during the operation [47]. The differences between the above studies on the relationship between centration methods and the EOZ may be attributed to differences in patients’ refractive status, kappa angle, and postoperative decentration measurement methods.…”
Section: Evaluation Of Eozmentioning
confidence: 99%
“…Huang et al [26] even found that the decentration of EOZ centroid in both eyes was different (the right eye shifted superior while the left eye shifted to the nasal side), although both eyes were centered on the CV by the TFM method. The latest research showed that the TFM center can simulate the position of the CV accurately and indicated that the decentration of EOZ after the operation can be predicted in advance by observing the change of the TFM center during the operation [47]. The differences between the above studies on the relationship between centration methods and the EOZ may be attributed to differences in patients’ refractive status, kappa angle, and postoperative decentration measurement methods.…”
Section: Evaluation Of Eozmentioning
confidence: 99%